2019
DOI: 10.1038/s41598-018-37316-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential anti-tumour effects of MTH1 inhibitors in patient-derived 3D colorectal cancer cultures

Abstract: Reactive oxygen species (ROS) function as second messengers in signal transduction, but high ROS levels can also cause cell death. MTH1 dephosphorylates oxidized nucleotides, thereby preventing their incorporation into DNA and protecting tumour cells from oxidative DNA damage. Inhibitors of MTH1 (TH588 and (S)-crizotinib) were shown to reduce cancer cell viability. However, the MTH1-dependency of the anti-cancer effects of these drugs has recently been questioned. Here, we have assessed anti-tumour effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Kawamura et al. 26 , 31 , 47 , 48 have suggested that TH287 and TH588 might display their antitumor activities through off-target effect by suppressing tubulin polymerization, whereas these inhibitors were subsequently proved to activate in a different manner as compared to anti-microtubule agent. Indeed, it was recently demonstrated that MTH1 could bind tubulin and promote the progression of mitosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamura et al. 26 , 31 , 47 , 48 have suggested that TH287 and TH588 might display their antitumor activities through off-target effect by suppressing tubulin polymerization, whereas these inhibitors were subsequently proved to activate in a different manner as compared to anti-microtubule agent. Indeed, it was recently demonstrated that MTH1 could bind tubulin and promote the progression of mitosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…And fourth, mice lacking MTH1 show a small but significant increase in spontaneous cancers 10 . A number of alternative mechanisms have been suggested for the anti-cancer effects of TH588 including lipophilicity-related effects, isoform-specific MTH1 targeting, tubulin depolymerization, oxidative damage, and downregulation of the PI3K-Akt-mTOR axis 5,6,1114 , but the question remains unresolved 12,15 . There are no reports on the use of unbiased screens to define genes and pathways that underlie TH588’s effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a number of studies have shown that MTH1 levels correlate with greater malignancy and poor prognosis in resected human lung tumors [43], colorectal tumors [44], and esophageal squamous cell carcinoma [45], and with greater frequency of ulcerative colitis-associated tumors [46]. Importantly, multiple studies have now shown that MTH1 depletion or inhibition increases genomic instability and DNA damage in cancer cells [8,19,40,[47][48][49][50]. Yet, recently developed MTH1 inhibitors and deletion of MTH1 by CRISPR/cas9 have been reported to have little, if any, impact on the proliferation of cancer cells in culture [51][52][53], further complicating our understanding of MTH1's role in cancer cell growth.…”
Section: Mth1 Function In Normal and Cancer Cellsmentioning
confidence: 99%